Pengaruh Brand Awareness, Promotion, Consumer Behaviour terhadap Purchase Intention pada Esperto Barista Course Jakarta Barat - Julian Bongsoikrama; Agus Sriyanto; Ajeng Larassati (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The purpose of this research is to find out the influence of Brand Awareness, Promotion, and Consumer Behaviour on Purchase Intention. This research is an explanatory research. The population used in this research are the customers of Esperto Barista Course, which is 1,202 people in total. Data collected using questionnaire. While sampling method used is simple random sampling with 100 respondents. Data is analyzed using SPSS 20. The result of this research is brand awareness affects the purchase intention, promotion affects the purchase intention, and consumer behavior affects the purchase intention. The findings of this study are in line with previous research, which states that brand awareness plays a critical role in shaping consumers' perception and trust toward a product or service. High brand awareness increases the likelihood of consumers considering the brand when making purchasing decisions. Moreover, effective promotional strategies significantly increase visibility and stimulate interest, which can lead to higher purchase intentions. In the context of Esperto Barista Course, promotional activities such as discounts, online advertisements, and social media marketing have shown a positive influence on attracting potential customers. Furthermore, consumer behavior—shaped by factors such as lifestyle, motivation, perception, and learning—demonstrates a direct relationship with purchase intention. The more a brand aligns with the values and expectations of its target consumers, the more likely they are to make a purchase. In this study, it was observed that respondents who had a strong personal interest in coffee culture and barista skills were more inclined to enroll in the course. These insights are valuable for Esperto Barista Course in refining their marketing strategies, aligning brand messaging with consumer values, and optimizing promotional tools to enhance customer engagement and conversion.